Interlinking motifs and entropy landscapes of statistically interacting particles - Lu, P.; Liu, D.; Müller, G.; Karbach, M. (Condensed Matter Physics, 2012)
The s=1/2 Ising chain with uniform nearest-neighbor and next-nearest-neighbor coupling is used to construct a system of floating particles characterized by motifs of up to six consecutive local spins. The spin couplings cause the assembly of particles which, in turn, remain free of interaction energies even at high density. All microstates are configurations of particles from one of three different sets, excited from pseudo-vacua associated with ground states of periodicities one, two, and four. The motifs of particles and elements of pseudo-vacuum interlink in two shared site variables. The statistical interaction between particles is encoded in a generalized Pauli principle, describing how the placement of one particle modifies the options for placing further particles. In the statistical mechanical analysis arbitrary energies can be assigned to all particle species. The entropy is a function of the particle populations. The statistical interaction specifications are transparently built into that expression. The energies and structures of the particles alone govern the ordering at low temperature. Under special circumstances the particles can be replaced by more fundamental particles with shorter motifs that interlink in only one shared site variable. Structures emerge from interactions on two levels: particles with shapes from coupled spins and long-range ordering tendencies from statistically interacting particles with shapes. Використовуючи s = 1/2 iзингiвський ланцюжок з однорiдною взаємодiєю найближчих i наступних за найближчими сусiдiв, побудовано систему незафiксованих частинок, якi характеризуються мотивами шести послiдовних локальних спiнiв. Взаємодiя спiнiв спричиняє групування частинок, якi, в свою чергу, не залежать вiд енергiй взаємодiї навiть при високiй густинi. Всi мiкростани утворенi конфiгурацiями частинок з одного iз трьох рiзних наборiв, якi вiдповiдають збудженням псевдовакуумiв, що пов’язанi iз основними станами перiодичностi один, два i чотири. Мотиви частинок i елементи псевдовакууму об’єднуються в двох спiльних вузлових змiнних. Статистична взаємодiя мiж частинками є закодованою в узагальненому принципi Паулi, що описує як розмiщення одної частинки змiнює можливостi для розмiщення подальших частинок. В статистично механiчному аналiзi довiльнi енергiї можуть ставитись у вiдповiднiсть всiм сортам частинок. Ентропiя є функцiєю заселеностi частинок. Особливостi статистичної взаємодiї прозоро вбудованi в цей вираз. Енергiї i структури частинок виключно визначають впорядкування при низьких температурах. За особливих умов частинки можуть бути замiненi фундаментальнiшими частинками з коротшими мотивами, що взаємозв’язуються однiєю спiльною вузловою змiнною. Зумовленi взаємодiєю структури виникають на двох рiвнях: частинки з формами, якi утворенi взаємодiючими спiнами, i тенденцiї до далекосяжного впорядкування частинок з формами, якi статистично взаємодiють.